Inventory of novel approaches to seed quality assurance mechanisms for vegetatively propagated crops (VPCs) in seven African countries - Sulle, E.; Pointer, R.; Kumar, P. Lava; McEwan, M. (International Potato Center, 2022)
This paper provides an inventory of novel approaches to and mechanisms for quality assurance of the seeds of vegetatively produced crops (VPCs). It explores to what extent seven African countries (Ethiopia, Kenya, Malawi, Nigeria, Tanzania, Uganda and Zambia) are decentralising and integrating VPC seed systems, in terms of regulations governing the sector, methods of seed production, and methods of seed inspection and certification. It consolidates existing data and presents new data on decentralised seed quality assurance (SQA) approaches for VPCs in these seven selected countries. It makes relevant information readily available for policy dialogue on appropriate and inclusive SQA approaches, by providing an assessment of (i) the extent to which SQA has been decentralised, i.e., the extent to which third-party accredited inspectors have been deployed; (ii) countries’ use of e-certification platforms; (iii) the involvement of seed producer groups and cooperatives in SQA; and (iv) any novel approaches to disease diagnostics or other relevant aspects of SQA. The paper uses different, appropriately sequenced methods to ensure the different methods complement each other to offset the disadvantages of each method. These include a comprehensive literature review, an online survey, and key informants’ virtual interviews. These are complemented by expert interviews, especially with both IITA and CIP experts based in Tanzania, Uganda, and Ethiopia plus one CIP expert with overall knowledge of the project countries in Africa. Based on an online survey completed by officials from regulatory agencies from eight countries, and follow-up interviews with seed certification officials and researchers in the seed sector, the paper finds that almost all studied countries have some sort of decentralised seed production system in place, allowing large-scale companies, medium-semi-commercial companies and small holder farmers opportunities to produce both quality declared and certified seeds. These decentralised seed production systems may be regarded as novel, in that they deviate from the standard seed system practices proposed at international level, which focus on enforcing certified seed production. Further, the novelty is based on different countries adopting different processes because of different local constraints and different government/political structures. Such novelty is necessary in the African context of, inter alia, poor infrastructure for transporting VPC seeds long distance and limited technical skills for certifying seed. The innovative approaches chosen by these African countries are suitable for VPC seeds like those of cassava, sweetpotato, bananas, yams and potato – all of which have bulky and perishable planting materials. The paper shows that it is possible to make decentralised VPC seed systems a reality in the right circumstances, and that in some cases countries have already made strides in doing so. However, several gaps exist in different countries, all of which need to be addressed. They include problems such as (i) legislation and regulations not specifically considering the quality assurance requirements of VPCs; (ii) shortages of trained staff throughout the system, but especially in far-flung areas; (iii) unavailable or inadequate training materials and handbooks; (iv) inadequate resources at local level, including support for inspection equipment and resources (e.g., vehicles); (v) poor monitoring and administration capacity in farmers’ cooperatives/associations; and (vi) poor consideration given to gender empowerment. Each of these and other issues are discussed throughout the report and in the recommendations at the end of the document. Stakeholders in the VPC sectors need to address key challenges facing VPC seed producers and users such as the lack of specific regulations for VPCs and standards, especially in the countries which are either still developing such standards and regulations, or entirely do not have such tools in place. The absence of crop specific guidelines and standard operating procedures result in (i) low capacity to produce quality VPC seed, (ii) poor storage and handling facilities for seed and (iii) inadequate experience, technical skills and training among the seed inspectors and certifying officials from state seed regulatory agencies, especially lack of staff specialised in certifying VPCs. Simple, flexible and less bureaucratic systems are much more desirable for developing countries, even while countries must maintain a focus on quality control and quality assurance mechanisms within the legal provisions of seed laws, including those of novel approaches (Loch and Boyce, 2001). Quality control and quality assurance are important preconditions for ensuring the availability of planting materials and for piloting novel approaches such as decentralised seed production and quality control approaches. It is thus important for countries to mainstream and scale up sustainable quality assurance systems that work by establishing context-appropriate seed regulatory frameworks. While individual farmers, farm-based associations, farmer cooperatives and private companies have invested and continue to invest in production of VPC seeds, public investments in this sector are needed to realise wider system change and impact. Because VPC seeds are bulky, perishable and have high disease risks, many seed companies are not interested in these crops. Therefore, is important to secure political buy-in for decentralised VPC production and devolved VPC seed inspection so that states are encouraged to invest in supporting regulatory agencies and decentralised offices to deliver their services efficiently and effectively. In turn, this will allow farmers to secure the extension services they require. To ensure scalability and sustainability of novel approaches like the decentralisation of seed production and quality assurance, piloted initiatives must be sustained, including (i) for capacity development; (ii) providing adequate resources (competent personnel, funding and the necessary technologies like electronic platforms); and (iii) more importantly, the presence of an entrenched policy, legal and institutional framework that is implemented on the ground. As part of the remedy for these challenges, the paper recommends that engaged stakeholders in the VPCs sector provide targeted training of seed inspectors. In many countries, seed standards for VPCs and provisions in the law were designed based on the experiences of grain (maize) seeds, which have significant differences with VPCs. Therefore, seed inspectors need training for inspection of VPCs (i.e. varietal identification, crop specific pests and diseases). This can be complemented by capacity development efforts at different levels; for example, (i) training extension officers to undertake inspections and how to use relevant equipment (including any ICT devices); (ii) training seed producer associations on technical and governance/administrative aspects for ensuring equity, accountability and monitoring; and (iii) training seed producers to inspect their own seed and fields. Countries need to establish and scale up seed producers’ associations. In countries where seed producer associations are in place, they have shown to be cost-effective by mobilising fellow seed producers who need seed inspections to pay inspectors as a group instead of as individuals. This has in turn also driven the demand for inspection from the relevant authorities, because inspection activities such as these generate income for government agencies. With associations in place, it is possible to help seed producers and farmers to identify markets for both seed and produce, to create a virtuous cycle whereby producers buy improved seed because they have a market for their improved produce. Finally, stakeholders need to implement or scale up e-certification platforms like SeedTrackerTM to reduce the burden and costs associated with manual and physical activities related to seed inspection and certification. Where ICT systems such as SeedTrackerTM have not been implemented, roll these out in all countries, ensuring both that they are suitable for each country’s specific needs, and that they align with regional and international seed policy. In countries like Nigeria and Tanzania where SeedTrackerTM is in place, it is imperative that most of these tools are improved to address the current limitations. Meanwhile, achievements – including the use of successful ICT tools – need to be promoted through regular communication and dialogue at all levels, including between farmers, seed producers and breeders (about the preferred traits for improved varieties and any challenges farmers are facing), and between stakeholders (to ensure alignment on the goals of seed quality assurance, how to ensure quality, and how to address problems).